Optimization of the Gram Staining Method Based on Superparamagnetic Magnetic Nanobeads - Feng, Yuren; Ren, Zihe; Wu, Fuhua; Reichert, Annika; Lu, Yun (Journal of Environmental Accounting and Management, 2026)
Gram staining is a widely used method for bacterial identification, where an alcohol burner is used as the fixed step, which requires a high level of proficiency, while the open flame is a potential fire hazard. A rapid, convenient and alternative method is also vailable that does not require a microscope or alcohol burner. This method utilizes the adsorption capacity of magnetic nanobeads. Ferriferous oxide beads are made by means of the co-precipitation method and adsorb bacteria in suspension liquid after being coated on the surface. The staining process omits the “heat” step and the need for a microscope, and distinguishes bacteria through the observation of the color of the liquid. According to our results, the behavior of this magnetic material performs well with various types of microbes. In particular, the color is clear and is easily distinguishable.